Lafaz Ditinjau Dari Segi Hakikat Dan Majaz (Wacana Pengantar Studi) - Baidawi, Ahmad (Al-Fikru: Jurnal Ilmiah, 2021)
The essence and majaz are two words in the form of mutadhayyifan or relative term (relative terminology), in the sense of being two words which are always side by side and each word will enter into one of them. The scholars give different meanings to the words true and majaz. The difference is only in the formulation while the understanding is close together. What is meant by essence is a lafaz which is used according to its origin for a specific purpose. The purpose of lafaz was formulated by language transfer is to facilitate understanding in the use of the language. Whereas what is meant by majaz is First; Lafaz does not show the true meaning as desired by a language. Second; Lafaz is not according to its true meaning borrowed to be used in giving meaning to what is meant. Third; between the target of the meaning of lafaz used with the target borrowed from the meaning of lafaz there is a connection. In relation to law, the nature and essence are the same in terms of providing legal understanding. Legal conclusions can be drawn from a lafaz based on the intrinsic meaning created for that lafaz, whether lafaz is general or specific, an order or prohibition. Likewise, the legal conclusion can be drawn from a lafaz based on the meaning of majazi lent for lafaz.